A Nomogram Model for Predicting Recurrence of Stage I–III Endometrial Cancer Based on Inflammation-Immunity-Nutrition Score (IINS) and Traditional Classical Predictors - Jiang P; Wang J; Gong C; Yi Q; Zhu M; Hu Z (Dove Medical Press, 2022)
Peng Jiang,1 Jinyu Wang,1 Chunxia Gong,2 Qianlin Yi,1 Mengqiu Zhu,1 Zhuoying Hu1 1Department of Gynecology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 2Department of Gynecology, Chongqing Health Center for Women and Children, Chongqing, People's Republic of ChinaCorrespondence: Zhuoying Hu, Department of Gynecology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China, Email huzhuoying@sina.comObjective: The purpose of this study was to investigate the prognostic value of the inflammation-immunity-nutrition score (IINS) in patients with stage I-III endometrial cancer (EC) and establish a nomogram model to predict the recurrence of EC by combining IINS and traditional classical predictors.Methods: Seven hundred and seventy-five patients with stage I-III EC who underwent initial surgical treatment at the First Affiliated Hospital of Chongqing Medical University were included in this study as the training cohort. In the training cohort, IINS (0- 3) was constructed based on preoperative C-reactive protein (CRP), lymphocytes (LYM), and albumin (ALB). Univariate and multivariate Cox regression analysis were used to screen independent predictors associated with recurrence of EC for developing the nomogram model. Internal validation of the model was performed in the training cohort by using the C-index and calibration curve, while external validation of the model was performed in another cohort (validation cohort) of 491 patients from the Second Affiliated Hospital of Chongqing Medical University.Results: IINS was successfully constructed, and survival analysis showed that patients with high IINS had a worse prognosis. Multivariate analysis showed that IINS, age, FIGO stage, pathological type, myometrial invasion, lymphatic vessel space invasion (LVSI), Ki67 expression, estrogen receptor (ER) expression, and P53 expression were significantly associated with shorter recurrence-free survival, and then a nomogram model for predicting the recurrence of EC was successfully established. The internal and external calibration curves of the model showed that the model fit well, and the C-index (0.887 in training cohort and 0.883 in validation cohort) showed that the model proposed in this study had better prediction accuracy than other prediction models.Conclusion: IINS may be a strong predictor of prognosis in patients with EC. The nomogram model incorporated into the IINS can better predict the recurrence of EC than the traditional models.Keywords: inflammation-immunity-nutrition score, IINS, nomogram model, predict, endometrial cancer, recurrence